Narrow Band Deep Red Photoluminescence of Y2Mg3Ge3O12:Mn4+, Li+ Inverse Garnet for High Power Phosphor Converted LEDs. (21st September 2017) - Jansen, T.; Gorobez, J.; Kirm, M.; Brik, M. G.; Vielhauer, S.; Oja, M.; Khaidukov, N. M.; Makhov, V. N.; Jüstel, T.
Abstract : This work concerns a novel red emitting Mn 4+ doped phosphor showing an extraordinarily high thermal quenching temperature. The composition Y2 Mg3 Ge3 O12 :Mn 4+, Li + exhibits efficient red photoluminescence peaking at 658 nm, which can be assigned to the 2 Eg → 4 A2g intraconfigurational transition of Mn 4+ ([Ar]3 d 3 configuration) located at the octahedral site in the garnet structure. Photoluminescence properties, such as temperature dependence of the luminescence intensity and luminescence lifetime are presented. Additionally, the band structure of the undoped host material were treated with Density Functional Theory (DFT) and evaluated with UV-reflectance spectroscopy. Furthermore, the energy levels of the Mn 4+ ion in the Y2 Mg3 Ge3 O12 host were calculated with the exchange charge model of crystal field theory and compared to those obtained experimentally from luminescence studies.